2011
DOI: 10.1128/jb.00045-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequences of Two Staphylococcus aureus Ovine Strains That Induce Severe (Strain O11) and Mild (Strain O46) Mastitis

Abstract: Staphylococcus aureus is a major etiological agent of mastitis in ruminants. We report here the genome sequences of two ovine strains that were isolated from gangrenous (strain O11) and subclinical (strain O46) ewe mastitis. Both strains belong to the same clonal complex. Despite this close genotypic relationship, the two isolates were shown to reproducibly induce highly divergent types of infections, either severe (O11) or mild (O46) mastitis, in an experimental ewe model.Staphylococcus aureus is one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The animal-specific leukocidin, lukM/lukF-P83 , was absent from both, hedgehog and human isolates [7], although it has been observed in (methicillin susceptible) sheep and rat isolates of CC130 [7], [25]. The “ etD2 ” exfoliative toxin homologue gene has been found in genome sequences of human and animal strains of CC130 [7], [25] as well as in the animal-specific staphylococcal species Staphylococcus hyicus (where it was named “ shetb ” ¸ GenBank AB036767.1) and Staphylococcus pseudintermedius (“ exi ” or “ expb ”; GenBank AB489850.1 and AB569087.1). A formation of skin blisters and exfoliation upon injection into neonatal mice has been observed [30] and a role in canine pyoderma has been suggested [31] as well as a role in exudative epidermitis of pigs [32].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The animal-specific leukocidin, lukM/lukF-P83 , was absent from both, hedgehog and human isolates [7], although it has been observed in (methicillin susceptible) sheep and rat isolates of CC130 [7], [25]. The “ etD2 ” exfoliative toxin homologue gene has been found in genome sequences of human and animal strains of CC130 [7], [25] as well as in the animal-specific staphylococcal species Staphylococcus hyicus (where it was named “ shetb ” ¸ GenBank AB036767.1) and Staphylococcus pseudintermedius (“ exi ” or “ expb ”; GenBank AB489850.1 and AB569087.1). A formation of skin blisters and exfoliation upon injection into neonatal mice has been observed [30] and a role in canine pyoderma has been suggested [31] as well as a role in exudative epidermitis of pigs [32].…”
Section: Discussionmentioning
confidence: 97%
“…The DNA sequence of a novel exfoliative toxin homologue, putatively named etD2 , that was detected as part of the present study in an Irish CC130 genome sequence [7] as well as in two other CC130 genomes (GenBank accession number AEUQ01000009.1, bases 161312 to 162153 and AEUR01000016.1, bases 44379 to 45221 [25]) was submitted to GenBank under accession number HF563069. The presence of this gene in both isolates was investigated by PCR with primers as listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Drug susceptibility data were collected from the following sources: (i) publications issued together with the fully sequenced genomes: USA300_TCH1516 and USA300_TCH959 [28], MRSA252 and MSSA476 [29], 04-02981 [30], T0131 [31], ST398 [32], COL [33], JKD6008 [34], 16 K [35], TW20 [36], Newman [37], RN4220 [38], O46 and O11 [39], RF122 [40], Mu3 [41], MRSA252 [29], CF-Marseille [42], N315 and Mu50 [43], MW2 [44], MSHR1132 [45], ECT-R_2 [46], JH1 and JH9 [17], ED98 [47], JKD6159 [48], LGA251 [49], ED133 [50]; (ii) NARSA project http://www.narsa.net; (iii) email exchange with the authors of publications related to strains ST398 and TW20; and (iv) other publications found by searching of related literature [21,23,33,37,51-98]. The complete collected phenotype data are available in the supplementary table (additional file 1).…”
Section: Methodsmentioning
confidence: 99%
“…S. aureus O46 was isolated from a ewe diagnosed with mild mastitis (Le Marechal et al 2011) and was cultivated overnight under microaerophilic conditions, at 37°C, in Mueller-Hinton (MH) media.…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%